Purification and Electrophoretic analysis of Extracellular Alkaline Phosphatase from bulb extracts of Urginea species - Misra, Banani; Kameshwari, M.N. Shiva (International Journal of Scientific Research in Biological Sciences, 2018)
Alkaline phosphatase was purified from three species of Urginea collected from different regions of India, Urginea wightii (Yediyur), Urginea indica(Karwar) and Urginea polyphylla (Castle rock Poona). The procedure followed for purification were Salt precipitation, Dialysis, ion exchange and Gel filtration method. Lowry’s method was used to estimate the Protein concentrations. The purified enzyme was subjected to 12.5% SDS-PAGE for molecular determination of Urginea species. The molecular weight of the protein band obtained was nearly 46 kDa in Urginea indica but Urginea wightii and Urginea polyphylla the protein band obtained was approximately 43kDa. The enzyme activity in these three-species varied. In Urginea indica it was found to be more about 0.152 U/ml while in Urginea wightii showed 0.05U/ml enzyme activity and 0.106 U/ml. in Urginea polyphylla.